2015
DOI: 10.1039/c5ra16900c
|View full text |Cite
|
Sign up to set email alerts
|

A Raman spectroscopic investigation of speciation in La2(SO4)3(aq)

Abstract: Raman spectroscopic measurements have been made of aqueous solutions of La(ClO 4 ) 3 , La 2 (SO 4 ) 3 , and Na 2 SO 4 in water and heavy water, in the terahertz frequency region (40-1400 cm À1) and down to low , the n 1 -SO 4 2À band in La 2 (SO 4 ) 3 (aq) showed systematic differences from that in Na 2 SO 4 (aq). This is consistent with a n 1 -SO 4 2À band at 983.3 cm À1 that can be assigned to the existence of an outer-sphere complex (OSCs). The observed change of the degree of sulfato-complex formation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…For all of the present Ln 3+ salts, the formation of CIPs has been claimed in the literature, see for example the reviews of Choppin, 22 Wood, 23 and of Smirnov and Trostin, 24 as well as recent publications of Rudolph and Irmer. 76,77 Such claims are at first glance at variance with the present DRS results, so it might be argued that the present assignment of the IP modes is incorrect. However, the observed relaxation times of LaCl 3 (aq) (t 1 E 320 ps), La(NO 3 ) 3 (aq) (t 2 E 230 ps) La 2 (SO 4 ) 3 (aq) (t 1 E 650 ps, t 2 E 140 ps), Eu(NO 3 ) 3 (aq) (t 1 E 140 ps), and Eu 2 (SO 4 ) 3 (aq) (t 1 E 420 ps, t 2 E 90 ps) (Tables S6-S10, ESI †) are definitely too large to be CIPs (t E 20-50 ps).…”
Section: Formation Of Cipscontrasting
confidence: 40%
“…For all of the present Ln 3+ salts, the formation of CIPs has been claimed in the literature, see for example the reviews of Choppin, 22 Wood, 23 and of Smirnov and Trostin, 24 as well as recent publications of Rudolph and Irmer. 76,77 Such claims are at first glance at variance with the present DRS results, so it might be argued that the present assignment of the IP modes is incorrect. However, the observed relaxation times of LaCl 3 (aq) (t 1 E 320 ps), La(NO 3 ) 3 (aq) (t 2 E 230 ps) La 2 (SO 4 ) 3 (aq) (t 1 E 650 ps, t 2 E 140 ps), Eu(NO 3 ) 3 (aq) (t 1 E 140 ps), and Eu 2 (SO 4 ) 3 (aq) (t 1 E 420 ps, t 2 E 90 ps) (Tables S6-S10, ESI †) are definitely too large to be CIPs (t E 20-50 ps).…”
Section: Formation Of Cipscontrasting
confidence: 40%
“…In aqueous La 2 (SO 4 ) 3 solutions, which are quite dilute because of the sparingly soluble solute, the sulfato complex formation could, nevertheless, be detected in solutions as dilute as 10 -3 mol·L -1 . The breathing mode of the La 3+ of the sulfato-complex, [La(OH 2 ) n SO 4 ] + , is down shifted by 31 cm -1 compared with the breathing mode of the non-complexed, fully hydrated [La(OH 2 ) 9 ] 3+ species with a 1 value at 343 cm -1 [42].…”
Section: Resultsmentioning
confidence: 98%
“…Experimental studies have indicated that REE-SO 4 2− complexes play a significant role in saturated aqueous solutions containing quartz due to REEs' close association with SO 4 2− ions [189], which can be attributed to the breakdown of SiO2 at high temperatures facilitating sulfate dissolution and enhancing the binding between REEs and SO 4 2− ions. Rudolph and Irmer (2015) [191] confirmed the presence of LaSO 4 + in a solution at 100 °C through in situ Raman observation, although La(SO 4 ) 2 − was not detected. Wan observed diverse complex forms of REE-SO 4 2− at high temperatures including REE(SO 4 ) 2…”
Section: Ree Sulfate Complexmentioning
confidence: 91%